All-Optical Tunable Filter With a Graphene-Buried Long-Period Waveguide Grating - Lianzhong Jiang; Wenfan Jiang; Kin Seng Chiang (IEEE Photonics Journal, 2023)
We demonstrate low-power all-optical tunable filters with long-period gratings formed in graphene-buried polymer waveguides, where the heat generated by graphene's absorption of the TE-polarized pump light serves to tune the TM-polarized resonance band. Our experimental gratings designed for operation at ∼1550 nm and pumped at 980 nm, which contain ∼6-mm long graphene, achieve a tuning efficiency of approximately –0.7 nm/mW, which corresponds to a ∼20-nm blue shift in the resonance wavelength with a pump power lower than ∼30 mW. Our grating can also serve as an all-optical switch when operated at a fixed wavelength, which can provide an extinction ratio larger than 20 dB with a pump power lower than 30 mW at a response time of ∼2.0 ms. The graphene-buried grating platform can be further explored for the development of a wide range of all-optical control devices.